The Effectiveness of Project-Based Learning and Problem-Based Learning Models on Students' Mathematical Creative Thinking Abilities Viewed From Learning Motivation - Khoirun Nisa, Rahma Lutfiya; Waluyo, Mohammad (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
The purpose of this research is to achieve an understanding of how teaching methods influence innovative thinking skills, examining the influence of learning motivation on creative thinking abilities, as well as examining the influence that occurs on creative thinking abilities due to the interaction between the learning model and learning motivation. The chosen research method is experimental. The research sample involves students from class VIII.7 and class VIII.9 of SMP N 2 Rembang, totaling 64 students. The data collection technique applied is through tests. Two-way ANOVA tests are applied in the data analysis. The results of this study indicate that there is a significant partial influence between the learning model and learning motivation on students' creative thinking abilities, where high learning motivation makes students excel in learning compared to other learning motivations. Additionally, there is also a mutually interactive relationship between learning models and learning motivation on creative thinking abilities.